Correction: CO2 conversion in a dielectric barrier discharge plasma: N2 in the mix as a helping hand or problematic impurity?. Issue 2 (26th January 2022) - Snoeckx, R.; Heijkers, S.; Van Wesenbeeck, K.; Lenaerts, S.; Bogaerts, A.
Abstract : Correction for 'CO2 conversion in a dielectric barrier discharge plasma: N2 in the mix as a helping hand or problematic impurity?' by R. Snoeckx et al., Energy Environ. Sci., 2016, 9, 999–1011, DOI: ; 10.1039/C5EE03304G .